Frequency of multi-vessel disease and its association with N Terminal-Pro Brain Natriuretic Peptide Levels among patients with First ST-Elevation Myocardial Infarction. - Sheikh, Kaleem Ullah; Sarfaraz, Abeer; Sarfaraz, Sana; Zehra, Aemon; Amir, Mohad; Amir, Haad (Nepalese Heart Journal, 2024)
Background and Aims: To determine the frequency of multi-vessel disease among patients with First ST-Elevation Myocardial Infarction and to identify the cutoff value of N Terminal-Pro Brain Natriuretic Peptide (NT-proBNP) for diagnosis of multi-vessel disease. Methodology: A descriptive cross-sectional study was conducted in the Department of Cardiology at a tertiary care hospital from September 2021 to February 2022. The study included 150 patients who presented to the emergency room with first ST-elevation myocardial infarction and preserved ejection fraction. NT-proBNP levels were tested within 12 hours of hospital admission. The severity of coronary artery disease was assessed by the number of vessels affected labeled, the luminal diameter narrowing and the syntax score. Results: The mean age of participants was 60.60±11.1 years. 76% were men, 53.3% of the participants had hypertension, 44% had type 2 diabetes, and 14% were smokers. The mean BMI of the patients was 27.86±3.86. The mean ejection fraction of the patients was 50±4.5.Single-vessel disease was present in 47 (31%) and 103 (69%) had multi-vessel disease. The mean NT-proBNP level in single-vessel disease was 561.34 pg/mL, and in multi-vessel disease, it was 1640.65 pg/mL. Raised levels of NT-proBNP were significantly associated with the severity of coronary artery disease. (P-value <0.05). The optimal cut-off value of NTpro-BNP for ruling out multiple vessel disease was 947.50 pg/mL at 81% of sensitivity. Conclusion: Pro-BNP is a valuable biomarker in assessing the severity of coronary artery disease in STEMI patients. Its levels have been shown to correlate with the degree of CAD severity including multi-vessel involvement.